The Effect of Variations in Drying Time and Drying Methods on Paint Coating Gloss Value Using a Multifunction Spray Booth - Bernatan, Juda; Utama, Firman Yasa (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Sand This study aims to analyze the effect of drying methods on drying time and gloss results during the painting process using a multifunction spray booth. Three drying methods tested were natural drying, forced air drying, and drying with a light bulb. The sample used was galvanized iron plates painted with Pilox spray paint and clear coat, then dried according to the applied method. Drying time was measured using a stopwatch, while gloss was tested using a gloss meter. The results showed that the light bulb method performed the best, with the highest gloss at all drying times tested. At drying times of 5 minutes, 10 minutes, and 15 minutes, the light bulb method produced 97.5 GU, 97.1 GU, and 96.9 GU, respectively. Forced air drying produced a gloss of 85.5 GU at 5 minutes, 87.7 GU at 10 minutes, and 88.9 GU at 15 minutes. Although its drying time was shorter than natural drying, the gloss produced was lower. Natural drying required a longer time of 15.42 minutes, with gloss results of 75.5 GU at 5 minutes, 78.9 GU at 10 minutes, and 85.7 GU at 15 minutes. From these results, it can be concluded that drying with the light bulb method is the best method in terms of both drying time and gloss quality, making it highly suitable for application in both industrial and small workshop scales.